PROSES PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2004 TENTANG PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Gaudensia Mariana; Dipo Wahyoeno (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This research is a normative type of research using various existing legal approaches. This research focuses on the formulation of the problem, As an Industrial Relations Dispute Procedure is based on Law No. 2 of 2004 on Industrial Relations Dispute Efforts. According to Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes, differences of opinion cause conflicts between employers and workers or a combination of employers and workers/employees or trade unions/trade unions. Article 2 of Law No.2 of 2004 states that the types of labor disputes are litigation, disputes of interest, disputes over the termination of employment, and union/union disputes in only one company. From the results of this study, it is known that three methods that can be applied to resolve industrial relations disputes are bipartite, tripartite, and arbitration